Customers’ Perceptions of Their Satisfaction Toward Online Shopping VS. In-Store Shopping in Angeles City, Philippines - Maricel Capitulo; Chere’ Yturralde (Research Synergy Foundation, 2025)
This study primarily focused on the variables, that is, the perceptions of customer satisfaction between online and in-store shopping. By comparing these two shopping modes, this study brought the issue of customer satisfaction into focus on the shopping experience. The objective of the study is to analyze and examine the in-store and online shopping experiences of customers in terms of customer satisfaction, to determine the sociodemographic profile of the respondents, and to describe how satisfied they were with both in-store and online shopping. The survey established that more than half were between the ages of 18 and 30, and most were females, while a good number were single. A greater number of people are employed, and their monthly income ranges from P10,000 to below, and they are college graduates. Respondents demonstrated a nearly equal preference for both in-store and online shopping, with a greater preference for in-store shopping regarding physically evaluating and comparing products. The results also revealed that, given the preferences in shopping mode by the respondents and their perceptions, differences in buyer buying patterns for in-store and online shopping exist but are minimal. This study differs from previous studies that have merely focused on the advantages of the online shopping experience. This study remains even in a post-pandemic situation because there is still a change in lasting consumer behavior and satisfaction between online and in-store shopping. Practically, it could be applied to business for better customer experience in the settings while theoretically, to understand what occurs within preferences on shopping throughout and after the disruption of the pandemic.